La Humanidad y la Divinidad de Cristo: las controversias cristológicas del s. IV y las cartas sinodales del Papa S. Dámaso (366-377) (Scripta Theologica, 2018)
The study examines the historical background to the earliest documents of Papal teaching in the area of Christology. It attempts an evaluation of their content comparing them with the writtings and work oj some Fathers such as St Atanasius and St Epiphanius. It is well known that the principal christological heresy oj the 4th Century is that of Apolinar ojf Laodicea. For long a defender of the orthodox faith set down in Nicea, Apolinar opposed Arius and defended the perfect and consubstantial Divinity of Christ. In effect Arius' error was both trinitarian and christological since he held that the Word, the second Person of the Trinity, was not "of the substance" of the Father and that the sufferings of Christ showed the "mutabily" of the Word. According to Arius, the Word was intimately united to a body (sarx) which constituted one nature with him. Apolinar, although holding that the Divinity of the Word is consubstantial with that of the Father, thought that the same is true as regards the Incarnation. He felt that the unity of Christ could only be maintained if one accepts that his Humanity came to be perfect as humaty through the hypostatic union. Apolinar developed to its final conclusions the theological model Logos-sarx proper to the Alexandrine school for reasons psychological (impeccability of Christ), soteriological (reparation of mankind in Christ), ontological (a perfect nature is necessarily an hipostasis) and philosophical (equivalence between individual nature and person). The tomus ad Antiochenos produced by the Council of Alexandria in 362 under the presidency of St Athanasius was a first warning against the excesses of the Logos-sarx scheme. Much more complete, however, was the reply of St Epiphanius in the Ancoratus and Panarion. He clearly detected all the elements of Apolinar's error. It was St Damasus who had the honour of definitively clarifying the subject in a series of documents of great theological and pastoral importance. There are two fundamental statements of Damasus: First, if Christ is the Saviour he must have assumed a complete (corpus, anima, sensus) and perfect human nature; second, human nature in itself as such is not necessarily inclined to sin. Christ is one, says Damasus, but at the same time he is God and men. In this sense Damasus developed the classic definition of Christ as perfectus Deus - perfectus homo and so prepared the way for the future definition of Chalcedonia.